Anisotropic compressional behavior of ettringite. (June 2019) - Comboni, Davide; Gatta, G. Diego; Lotti, Paolo; Merlini, Marco; Hanfland, Michael
Abstract: The high-pressure behavior of a natural ettringite [Ca6 Al2 (SO4 )3 (OH)12 ·27H2 O, a = 11.2104(2) Å, c = 21.4350(3) Å, sp. gr. P 31 c ] has been studied by single-crystal X-ray diffraction with a diamond-anvil cell up to 4.22 GPa, using the methanol:ethanol = 4:1 mixture as a hydrostatic pressure-transmitting fluid. The isothermal bulk modulus ( K 0 = − V (∂ P / ∂ V )) was found to be 26.6(5) GPa. Ettringite shows a significant anisotropic compressional pattern, being more compressible on (001) than along [001] ( i.e. the fibers growing axis), with K ( c )0 2 K ( a, b )0 . The mechanisms at the atomic scale, which govern the structure deformation, have been described by a series of structure refinements up to 2.3 GPa. The structure evolution in response to the applied pressure indicates a plausible densification of the hydrogen-bond network between the Ca(OH)4 (H2 O)4 polyhedra and the SO4 tetrahedra, which results in a softening and ultimately in a collapse of the whole structure at pressures > 3 GPa. Graphical abstract: Unlabelled Image Highlights: The anisotropic elastic behavior of ettringite has been investigated up to 4.2 GPa. Above 3 GPa, a sharp softening of the structure, mainly on the ab plane occurs. Such softening may be induced by a collapse of the hydrogen bonds network.